2018
DOI: 10.1080/13549839.2018.1463978
|View full text |Cite
|
Sign up to set email alerts
|

Urban sharing in smart cities: the cases of Berlin and London

Abstract: Addressing urban sustainability challenges requires changes in the way systems of provision and services are designed, organised and delivered. In this context, two promising phenomena have gained interest from the academia, the public sector and the media: "smart cities" and "urban sharing". Smart cities rely on the extensive use of information and communications technology (ICT) to increase efficiencies in urban areas, while urban sharing builds on the collaborative use of idling resources enabled by ICT in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 23 publications
0
31
0
1
Order By: Relevance
“…At the same time, there are synergies in smart-sustainable cities that either go beyond or could potentially go beyond broadly neoliberal 'business as usual'. Making urban data widely available, developing a city-scale 'Internet of Things' and mobilising smart and digital technologies has the potential to enhance social well-being, empower communities, reveal previously hidden urban environmental processes, enable resource and skills sharing, include citizens in co-creative governance processes, generate novel solutions to mundane urban problems, and underpin new models for more efficient use of idle assets (see Zvolska et al 2019;Menny, Voytenko Palgan, and McCormick 2018;McLaren and Agyeman 2015;Martin, Evans, and Karvonen 2018). But this also requires the careful application of ICT technologies to avoid empowering corporate interests within urban visioning and management and further excluding those already marginalised by prevailing technocratic and entrepreneurial forms of urban governance (Vanolo 2014;Söderström, Paasche, and Klauser 2014;Hollands 2016).…”
Section: Conclusion: Equity and Environment In The Smart-sustainablementioning
confidence: 99%
“…At the same time, there are synergies in smart-sustainable cities that either go beyond or could potentially go beyond broadly neoliberal 'business as usual'. Making urban data widely available, developing a city-scale 'Internet of Things' and mobilising smart and digital technologies has the potential to enhance social well-being, empower communities, reveal previously hidden urban environmental processes, enable resource and skills sharing, include citizens in co-creative governance processes, generate novel solutions to mundane urban problems, and underpin new models for more efficient use of idle assets (see Zvolska et al 2019;Menny, Voytenko Palgan, and McCormick 2018;McLaren and Agyeman 2015;Martin, Evans, and Karvonen 2018). But this also requires the careful application of ICT technologies to avoid empowering corporate interests within urban visioning and management and further excluding those already marginalised by prevailing technocratic and entrepreneurial forms of urban governance (Vanolo 2014;Söderström, Paasche, and Klauser 2014;Hollands 2016).…”
Section: Conclusion: Equity and Environment In The Smart-sustainablementioning
confidence: 99%
“…This is also recognised by Davidson and Infranca [26] when discussing the sharing economy as an urban governance challenge, pointing to the intrinsic dependences between sharing activities and specific urban conditions. Indeed, local or "city governments around the world are increasingly adopting policies to regulate some forms of sharing" [14]. Building upon a framework for urban climate governance developed by Bulkeley and Kern [12], Zvolska et al [14] suggested the different roles that cities assume when governing urban sharing are: governing by regulation, governing by provision, governing by enabling, and governing by consumption.…”
Section: Governing the Sharing Economymentioning
confidence: 99%
“…Indeed, local or "city governments around the world are increasingly adopting policies to regulate some forms of sharing" [14]. Building upon a framework for urban climate governance developed by Bulkeley and Kern [12], Zvolska et al [14] suggested the different roles that cities assume when governing urban sharing are: governing by regulation, governing by provision, governing by enabling, and governing by consumption. We will come back to this next, when discussing our analytical framework.…”
Section: Governing the Sharing Economymentioning
confidence: 99%
See 2 more Smart Citations